Role of insulin in management of type 2 diabetes mellitus - Patil, Sujay S.; Mehta, Manthan; Thakare, Vaishali; Shende, Shrikrishna; Shirure, Prashant A.; Swami, Onkar C. (International Journal of Research in Medical Sciences, 2017)
The prevalence of type 2 diabetes mellitus and its resultant morbidity and mortality is rapidly increasing. An important factor in reducing the microvascular complications of diabetes is strict glycemic control. Most patients require additional insulin therapy in spite of regularly taking oral anti-diabetic drugs. Though classically used later in the natural course of the disease, newer treatment guidelines suggest early initiation of insulin analogues. The discovery of insulin has been hailed as one of the most dramatic events in the history of diabetes, improving the life-span of most diabetics. Replacement insulin therapy should mimic physiological insulin release patterns. Modern insulin and its analogues have been developed to serve as an ideal replacement therapy. There are various insulin preparations available in the market and each of them has their own advantages and disadvantages. The modern insulin’s have been developed to overcome certain side effects of the older preparations. A range of insulin products are under development that aim to increase absorption prolong action and provide alternative delivery methods. Greater patient adherence is important since most patients are reticent about insulin therapy.  This review describes the role of insulin in the management of type 2 diabetes mellitus.